2019
DOI: 10.1111/jsr.12946
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic reactions during N3 sleep arousals in sleepwalking and sleep terrors: The chicken or the egg?

Abstract: Patients with sleepwalking episodes or sleep terrors (SW/ST) exhibit sudden abnormal behaviours arising from sleep, mostly from N3 sleep (American Academy of Sleep Medicine, 2014). Patients usually open their eyes, look around with a confused gaze, sit, stand, walk, talk, scream or flee their bed (Derry, Harvey, Walker, Duncan, & Berkovic, 2009). There is a continuum between the different behavioural patterns of arousal parasomnias. Specifically, the behavioural patterns of non-rapid eye movement (NREM) paraso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Another study under normal sleep conditions showed that arousals during slow-wave sleep in 38 predisposed individuals were associated with an abrupt heart rate acceleration ( 18 ). A similar finding was found for motor arousals during slow-wave sleep associated with sleepwalking or sleep terrors in 20 participants, with arousals being preceded by an abrupt heart rate acceleration ( 20 ). Overall, our present findings suggest that this activation prior to episode occurrence does not appear to extend to entire periods of slow-wave sleep.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Another study under normal sleep conditions showed that arousals during slow-wave sleep in 38 predisposed individuals were associated with an abrupt heart rate acceleration ( 18 ). A similar finding was found for motor arousals during slow-wave sleep associated with sleepwalking or sleep terrors in 20 participants, with arousals being preceded by an abrupt heart rate acceleration ( 20 ). Overall, our present findings suggest that this activation prior to episode occurrence does not appear to extend to entire periods of slow-wave sleep.…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, investigating autonomic nervous system functioning in sleepwalkers following a period of sleep deprivation may provide insights into the neural pathophysiological mechanisms involved in sleepwalkers' slow-wave sleep regulation. A few studies having measured heart rate in sleepwalkers found autonomic changes suggestive of an abrupt sympathetic activation before episodes, including during slow-wave sleep ( 18 20 ). These preliminary reports suggest that autonomic dysfunctions might play a role in pathophysiology of sleepwalking.…”
Section: Introductionmentioning
confidence: 99%
“…All HNIV sequences and time‐synchronized video recordings associated with N3 sleep interruptions during the VPSG were visually inspected by a single scorer (R.L.). Events characterized by sudden motor behaviours (raising the head or torso, sitting in bed or standing) and/or vocal or facial manifestations of confusion/disorientation, surprise or fear were defined as parasomniac episodes (Cataldi et al, 2022; Joncas et al, 2002; Ledard et al, 2019; Lopez et al, 2018), and were classified according to three clinical subtypes: (1) sleepwalking episodes when associated with ambulation; (2) sleep terror episodes characterized by abrupt arousals with expression of fear and/or screaming; (3) the parasomniac episodes that did not correspond to sleepwalking or sleep terror were classified as confusional arousals. The frequency of parasomniac episodes during the HNIV was estimated using: (1) the mean number of episodes (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…All HNIV sequences and time-synchronized video recordings associated with N3 sleep interruptions during the VPSG were visually inspected by a single scorer (R.L.). Events characterized by sudden motor behaviours (raising the head or torso, sitting in bed or standing) and/or vocal or facial manifestations of confusion/disorientation, surprise or fear were defined as parasomniac episodes (Cataldi et al, 2022;Joncas et al, 2002;Ledard et al, 2019;Lopez et al, 2018), and were classified according to three clinical subtypes:…”
Section: Behavioural Analysesmentioning
confidence: 99%
“…These changes are more marked than those associated to normal arousals or even with post‐apnea arousals. Of interest, while these changes were thought to occur at the exact time of confusional arousal (Schenck et al, 1998), a recent study analysis of instantaneous heart rate indicated that these adrenergic markers started to increase 3–4 s before the behavioural arousal (Ledard et al, 2020). This sequence was observed during N3 interruptions in normal controls too.…”
Section: Polysomnography Video and Brain Functional Imagingmentioning
confidence: 99%